Modern weapons and military equipment for issue 3-2023 - Vučković, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2023)
Project 863-706 Shenlong ("Divine Dragon"), Reusable Test Spacecraft; China Says It Conducted A Successful Suborbital Test Of A Reusable Spaceplane; X-37B Space Plane’s Microwave Power Beam Experiment Is A Way Bigger Deal Than It Seems Is China gliding toward a FOBS capability? Turkey’s ‘Drone Carrier’ Amphibious Assault Ship Enters Service THE WAR ZONE; Is Russia Using Its New Advanced Anti-Armor Missile In Ukraine?